Aslanova, Nigar - (:unkn) unknown (My University, 2026)
Nigar Aslanova graduated with honors from the Faculty of Mechanics and Mathematics of Baku State University in 1992, earning the qualification of Mathematician and Mathematics Teacher. In 1993, she entered the doctoral program at the Institute of Mathematics and Mechanics of the Azerbaijan National Academy of Sciences, where she completed her PhD in 1996. In 2013, she was awarded the degree of Doctor of Sciences in Mathematics for her dissertation on the spectra and traces of differential-operator equations. In 2018, she received the academic title of Professor. From 1996 to 2013, she held various research positions at the Institute of Mathematics and Mechanics of the Azerbaijan National Academy of Sciences. Since 2011, she has been a faculty member of the Azerbaijan University of Architecture and Construction (AzUAC), where she has served as Professor since 2015. Between 2013 and 2022, she was the Scientific Secretary of the Academic Council of AzUAC, and since 2022, she has been serving as Vice-Rector for Science and Innovation. In 2025, she was a Visiting Professor at the Fields Institute (Canada), and in 2026, she was awarded a Fields Research Fellowship to conduct research at the institute. Professor Aslanova is the author of more than 60 scientific publications, including 20 papers published in high-impact journals, as well as methodological works and two English-language textbooks. She is a member of the editorial boards of the Scopus-indexed journals Azerbaijan Journal of Mathematics and Transactions, has participated in and led several research projects funded by the Science Development Foundation of Azerbaijan, and has coordinated the Avicenna Project at the Azerbaijan University of Architecture and Construction.